ÙØ¹Ø§Ù„ÙŠØ© Ø·Ø±ÙŠÙ‚Ø© Ø§Ù„Ù…Ø¨Ø§Ø´Ø±Ø© Ø¨Ø§Ø³ØªØ®Ø¯Ø§Ù… Ù„Ø¹Ø¨Ø© Ø§Ù„ÙƒØ±Ø© Ø§Ù„Ø£Ø³Ø¦Ù„Ø© Ù„ØªØ±Ù‚ÙŠØ© Ù…Ù‡Ø§Ø±Ø© Ø§Ù„ÙƒÙ„Ø§Ù… - Muhammad Ihsan (Lughatu Ad-Dhat, 2020)
ABSTRACT As for the research method, which uses quantitative and experimental methods. The research design used is a quasi-experimental design (Quasi Eksperimental Design.). This study aims to find out: Is the direct method of using the question ball game an effective way to upgrade the speech skill of the seventh grade students of the Islamic middle school Nahdhat Al-Watan Krelico academic year 2019/2020. Based on the results of the independent test of the sample t above, we obtain the computational value t = 3,743 with significance level (p) 0.05 = 2.021. Based on the above computation, the computation of t is greater than table t, i.e. (3,743> 2.021) therefore, Ha is acceptable and Ho returns. This means that the direct method of using the question ball game is effective for improving speech skills among students of the seventh grade of the Islamic Middle School Nahdhat Al-Watan Kryliku for the academic year 2019/2020. Â Keywords: Direct Method, Ball Game Questions, and Speech Skill